Ice‐nucleating particle emissions from photochemically aged diesel and biodiesel exhaust - G. P. Schill; S. H. Jathar; J. K. Kodros; E. J. T. Levin; A. M. Galang; B. Friedman; M. F. Link; D. K. Farmer; J. R. Pierce; S. M. Kreidenweis; P. J. DeMott (Geophysical Research Letters)
Abstract Immersion‐mode ice‐nucleating particle (INP) concentrations from an off‐road diesel engine were measured using a continuous‐flow diffusion chamber at −30°C. Both petrodiesel and biodiesel were utilized, and the exhaust was aged up to 1.5 photochemically equivalent days using an oxidative flow reactor. We found that aged and unaged diesel exhaust of both fuels is not likely to contribute to atmospheric INP concentrations at mixed‐phase cloud conditions. To explore this further, a new limit‐of‐detection parameterization for ice nucleation on diesel exhaust was developed. Using a global‐chemical transport model, potential black carbon INP (INPBC) concentrations were determined using a current literature INPBC parameterization and the limit‐of‐detection parameterization. Model outputs indicate that the current literature parameterization likely overemphasizes INPBC concentrations, especially in the Northern Hemisphere. These results highlight the need to integrate new INPBC parameterizations into global climate models as generalized INPBC parameterizations are not valid for diesel exhaust.